2022
DOI: 10.3390/agriculture12070973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oregano (Lippia graveolens) Essential Oil as a Phytogenic Feed Additive on Productive Performance, Ruminal Fermentation, and Antioxidant Activity in Lamb Meat

Abstract: The objective of this study was to evaluate the inclusion of oregano essential oil (OEO) as a phytogenic feed additive in the diet of lambs on the productive performance, ruminal pH, ammoniacal nitrogen production, volatile fatty acids, nitrogen balance, carcass yield, backfat thickness, loin eye (Longissimus dorsi) area, shelf life, and antioxidant activity of the meat. Thirty-nine Suffolk × Hampshire lambs (19 ± 3.7 kg live weight) were used in a completely randomized design with three treatments (n = 13) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Also, in Chios lambs, administering oregano EO (1 mL/kg) of concentrated feed resulted in strong antioxidant effects, retarding lipid oxidation (MDA formation) in meat during refrigeration and long-term frozen storage [75]. However, similarly to Muñoz-Cuautle et al [74], in this experiment too, the EO administration did not result in improved final body weight, body weight gain, carcass yield, and tenderness of the Longissimus thoracis muscle. The supplementation of oregano EO at 300 mg/kg exerted an improved growth and slaughter performance in Sewa lambs, suggesting that this dose could have a fattening effect on lambs [63].…”
Section: Effects Of Essential Oils On Small Ruminant Productssupporting
confidence: 50%
See 1 more Smart Citation
“…Also, in Chios lambs, administering oregano EO (1 mL/kg) of concentrated feed resulted in strong antioxidant effects, retarding lipid oxidation (MDA formation) in meat during refrigeration and long-term frozen storage [75]. However, similarly to Muñoz-Cuautle et al [74], in this experiment too, the EO administration did not result in improved final body weight, body weight gain, carcass yield, and tenderness of the Longissimus thoracis muscle. The supplementation of oregano EO at 300 mg/kg exerted an improved growth and slaughter performance in Sewa lambs, suggesting that this dose could have a fattening effect on lambs [63].…”
Section: Effects Of Essential Oils On Small Ruminant Productssupporting
confidence: 50%
“…Muñoz-Cuautle et al [74] observed that oregano EO, at 0.02% and 0.04%, in the diet of Suffolk × Hampshire male lambs did not result in improved productive performance, backfat thickness and loin eye area; however, the antioxidant activity of lambs' meat was improved. In particular, the addition of 0.02% of oregano EO in the diet of growing lambs preserved the stability of the crude protein, and the improved antioxidant activity increased the shelf life of lamb meat.…”
Section: Effects Of Essential Oils On Small Ruminant Productsmentioning
confidence: 99%
“…Feeding strategies aiming to increase the concentration of PUFAs in meat may increase tissue susceptibility to oxidation and perioxidation [9]. In order to limit these processes, several authors have studied the association of plants and herbs having antioxidant properties due to the presence of bioactive compounds (i.e., terpenoids and phenylpropanoids), which are effective in lowering or delaying the occurrence of lipid oxidation [56,57]. Among these, oregano contains carvacrol, thymol, and terpinene, and is considered an alternative to antibiotics due to its antioxidant and antimicrobial properties [58,59].…”
Section: Discussionmentioning
confidence: 99%